The comparative study of quality of life among working women and homemakers taking care of psychiatric patients presenting in a tertiary care hospital, Patna - Singh, Vivek Pratap; Puria, Alka; Singh, Abhishek Pratap; Singh, Narendra Pratap; Goyal, Ekram (Asian Journal of Medical Sciences, 2021)
Background: In India, women are twice more likely to become caregivers than men. The quality of life (QOL) is the ability level to which an individual is healthy and able to enjoy life. Aims and Objective: To assess and compare QOL among homemaker women and working women giving care to patients suffering from psychiatric illnesses. Materials and Methods: This hospital-based, cross-sectional study was conducted on the caregivers who were recruited from out-door patient department of Psychiatry department of Patna Medical College and Hospital, Patna from January 1, 2021, to June 31, 2021. Women who were 30–55 years old, working or homemakers, and who were taking care of psychiatric patients diagnosed with Schizophrenia and Bipolar affective disorder of either sex. Caregivers were first degree relatives of patients. The estimated sample size was 140 (Group 1=70 homemaker women and Group 2=70 working women). Sociodemographic data were recorded using Sociodemographic Performa 1 and QOL was assessed using World Health Organization (WHO)-QoL-BREF. Results: WHO-QOL domain mean score for physical, psychological, social, and environmental of Group 1 was 12.42, 11.60, 12.24, 12.62 whereas 14.46, 13.28, 11.28, and 12.28 of Group 2 with statistically significant difference (P<0.05). Conclusion: In physical and psychological domain of QoL, working women scores were better than homemakers. QOL in working women caregivers was better than homemakers’ caregivers in social and environmental domains but statistically non-significant.